Analysis and process evaluation of metal dopant (Zr, Cr)-promoted Ga-modified ZSM-5 for the oxidative dehydrogenation of propane in the presence and absence of CO2. Issue 16 (6th April 2023) - Jawad, Abbas; Ahmed, Sura
Abstract : A systematic study of the comparative performances of 4% Ga-, 4% Zr-, and 1% Cr-impregnated H-ZSM-5 catalysts for oxidative dehydrogenation of propane in the presence and absence of CO2 is presented. Abstract : A systematic study of the comparative performances of 4% Ga-, 4% Zr-, and 1% Cr-impregnated H-ZSM-5 catalysts for oxidative dehydrogenation of propane in the presence and absence of CO2 is presented. It was found that methane, ethene, propene, butene, pentene, and BTX are the major products from all of these catalysts at various reaction temperatures (400–550 °C), WHSV, 4 kgcat s molC3 H8 −1 and feed gas, C3 H8 /N2 = 2.5/97.5 and C3 H8 /CO2 /N2 = 2.5/5/92.5; flow rate, 75 mL min −1 under atmospheric pressure for 10 h. The combination of material characterization and catalytic testing revealed that Ga-, Zr-, and Cr-doped H-ZSM-5 are excellent catalysts for this process, helping to achieve around 61% CO2 conversion. The co-doped Ga/H-ZSM-5 catalysts significantly enhanced the activity (65% propane and 61% CO2 conversion at 550 °C) among all the tested catalysts, with approximately 100% total selectivity 62% towards BTX and 26% towards propene, but with lower selectivity for methane, ethene, and pentene ( i.e., light hydrocarbons). TPR profiles indicated that the redox cycle between Cr(iii )O6 and Cr(vi )O4 played an important role in the dehydrogenation of C3 H6 over Cr/Zr–Ga/H-ZSM-5. CO2 could oxidize a part of the Cr(iii ) species to Cr(vi ) species under the reaction conditions used.